Socio-Demographic and Nutritional Determinants of Birth Weight in Coastal Areas: Determinan Sosio-demografikdan Gizi yang Berhubungan dengan Berat Badan Lahir Bayi di Daerah Pesisir - Juminten Saimin; Amalia N Azizah; Satrio Wicaksono (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective : To identify socio-demographic and nutritional determinant associated with birth weight in coastal areas. Method : A cross sectional study using simple random sampling method. Data of labour in coastal areas of Kendari City was analyzed. Total of 215 women who aterm delivery in Community Health Centre of Mata, Nambo and Abeli on January to December 2016 were included in this study. Birth weight was examined in association with independent variable as maternal age, education, occupation, husband’s job, parity, antenatal care, iron tablets consumption and upper arm circumference. Results : Most participants were aged 20-25 years old, primary education, as housewife, multiparity and husband work as self-employed. There was 8.9% low birth weight in coastal areas. Maternal age, education and ANC visits were significantly associated with birth weight (p < 0.05). Consumption of iron tablets and upper arm circumference were significantly associated with birth weight (p < 0.05). Conclusion :Maternal age, education and ANC visits were socio-demographic determinant that associated with birth weight. Iron tablets consumption and upper arm circumference were nutritional determinant that significantly associated with birth weight. Keywords : age, antenatal care, birth weight, education, iron tablets, upper arm circumference Abstrak Tujuan :Mengidentifikasi determinan sosio-demografik dan gizi yang berhubungan dengan berat badan lahir bayi di daerah pesisir. Metode :Penelitian potong lintangdengan pengambilan sampel secara simple random sampling. Dilakukan analisis terhadap 215 ibu hamil yang melahirkan bayi cukup bulan di wilayah kerja Puskesmas Mata, Nambo dan Abelipada bulan Januari sampai Desember 2016. Varia beli independen berupa usia ibu, tingkat pendidikan, pekerjaan, pekerjaan suami, paritas, antenatal care, konsumsi tablet besi dan ukuran lingkar lengan atas. Hasil :Responden terbanyak berusia 20-25tahun, berpendidikan rendah, bekerja sebagai ibu rumah tangga, multiparitas dan pekerjaan suami wiraswasta. Terdapat8,9% bayi BBLR. Terdapat hubungan yang bermakna antara usia ibu, tingkat pendidikan dan ANC dengan BBL (p < 0.05). Terdapat hubungan yang bermakna antara konsumsi tablet besi dan ukuran LILA dengan BBL (p < 0.05). Kesimpulan :Determinan sosio-demografik yang berhubungan dengan BBL adalah usia, tingkat pendidikan, dan ANC. Sedangkan determinan gizi yang berhubungan dengan BBL adalah konsumsi tablet besi dan ukuran LILA. Kata kunci: ANC, BBL, LILA, pendidikan, tablet besi, usia